Nursing care in Primary Care for patients with arterial hypertension (Research, Society and Development, 2020)
This study aimed to understand the prevalence of hypertension control and to analyze the educational strategies and actions developed by Primary Health Care professionals. It is an integrative literature review study, with a qualitative approach, carried out by searching for articles indexed in the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin Literature -American and Caribbean Health Sciences (LILACS). The inclusion criteria include literature review surveys covering the years 2010 to 2020. The exclusion criteria were duplicate, incomplete articles, abstracts, reviews, debates, experience reports and unavailable in full. 15 articles and 04 studies referring to health entities were analyzed. The results of the study found that several factors influence the prevalence of hypertension. Faced with this, UBS plays an important role in health promotion and prevention, thus providing health guidance aimed at changing habits, self-care and quality of life for chronic patients. We conclude then, the need for new implementations in the educational scope, health guidelines and strategies that match the reality of this target audience, providing the creation of bonds with the user, thus contributing to the development of health actions. In addition to identifying risk aspects that can support the development of this pathology, providing quality and resolving assistance with the assistance of a multiprofessional team articulated to solve health needs in Primary Health Care.